Intermetallic Growth and Shear Strength of SAC305/EN-Boron - Hardinnawirda, Kahar; Zetty Akhtar, Abd Malek; Siti Rabiatull Aisha, Idris; M., Ishak (Emerald Group Publishing Limited, 2016)
The paper aimed to study the effect of aging and cooling rate on the reliability of the solder joint using electroless nickel boron (EN-Boron) as a surface finish in the electronic packaging area.EN-Boron was plated on Cu substrate through electroless plating method. This process was followed by reflow soldering of a Sn-3.0Ag-0.5Cu solder alloy on metallized Cu substrate to form a joining. Then, the specimens were cooled using different cooling medium which were air (slow cooling) with 15.7°C/min and water (fast cooling) with 110.5°C/min. After that, the specimens were subjected to isothermal aging at 150°C for 0, 250, and 1000 hours. Finally, they went through a lap shear test following a standard of ASTM D1002. Optical microscope and SEM were used for IMC characterization. The type of IMC formed was confirmed by FESEM-EDX. The results showed that the IMC type changed from the combination of Ni3Sn4 and (Ni, Cu)3Sn4 after reflow soldering into fully (Ni,Cu)3Sn4 when aged for 1000 hours. The formation of (Ni,Cu)3Sn4 and Cu3Sn underneath the IMC layer played a role in reducing the shear strength of joining. Overall, water cooling was reported to provide higher shear strength of solder joint compared to air cooling medium. The shear strength between solder alloy and EN-Boron surface finish is comparable to the surface finish conventionally used.